Composite material rod surface protective coating polymer coating that can quickly harden at room temperature
By using polymer coatings composed of components A and components B, the problem of insufficient impact resistance of existing polyurea elastomer coatings is solved, and the effect of rapid hardening and efficient construction at room temperature is achieved, while improving the coating Salt spray resistance.
Patent Information
- Application Number
- CN202411718442.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-28
AI Technical Summary
When the coating thickness of existing polyurea elastomer coatings is certain, the impact resistance after spraying is difficult to meet the practical application requirements of high standards, and excessive addition of reinforced fillers may lead to a reduction in coating strength.
Using polymer coatings composed of components A and components B, the A components include polyether polyols, isocyanates, hexamethylene diisocyanates, dibutyl phthalate, and cetylpyridine bromide surface modification Chitosan modified zeolite complex and humic acid, component B includes polyetheramine and diethyltolyldiamine, and the mass ratio of the two is 1:1~1:3, and is prepared by vacuum dehydration and hot stirring reaction.
This polymer coating can harden rapidly at room temperature, shorten the construction time and curing cycle, improve construction efficiency, and improve the salt spray resistance and impact resistance of the coating through the combination of environmentally friendly raw materials and specific composites.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings and coatings, and in particular relates to a polymer coating which can quickly harden at room temperature and is a protective coating on the surface of a composite material rod. Background Art
[0002] Polyurea elastomer is a high-performance elastic material formed by the reaction of component A (isocyanate) and component B (amino compound). This material occupies a prominent position in many fields, especially in the architectural coatings industry, due to its simple preparation process, fast curing, hard coating, impact resistance, corrosion resistance and high strength. Recently, the environmental protection properties, low toxicity and pollution-free characteristics of polyurea elastomers have attracted increasing attention in the field of protective materials. In protective applications, in addition to the excellent physical strength of polyurea elastomers, they are also required to maintain good stability when subjected to impact, which is a high requirement for traditional polyurea products.
[0003] At present, there are usually two ways to improve the impact resistance of polyurea materials: one is to increase the content of hard segments in the polyurea system, and the other is to introduce reinforcing fillers. Although increasing the hard segment content can enhance the strength of polyurea, this will also increase the hardness of the material, affecting its flexibility under low temperature conditions, making it easy to break at low temperatures. Although such improvements can improve the impact resistance to a certain extent, when the coating thickness is constant, the impact resistance of the sprayed polyurea elastomer does not meet expectations and is difficult to meet the high standards of practical applications. Excessive addition of reinforcing fillers may cause microphase separation between the filler and the matrix when the material is impacted, thereby significantly reducing the strength of the coating, which is also difficult to meet the requirements of the protection field. Summary of the invention
[0004] The present invention aims to provide a composite material rod surface protective coating that can quickly harden at room temperature and is used to solve the problem of insufficient physical properties of the coating caused by reinforcing fillers in the prior art.
[0005] The present invention is achieved through the following technical solutions:
[0006] The composite rod surface protective coating is a polymer coating that can be quickly hardened at room temperature, and is composed of component A and component B, wherein component A includes, by mass: 40 to 60 parts of polyether polyol, 25 to 40 parts of diphenylmethane-4,4'-diisocyanate, 25 to 40 parts of hexamethylene diisocyanate, 3 to 10 parts of dibutyl phthalate, 1 to 10 parts of hexadecylpyridinium bromide surface-modified chitosan modified zeolite composite, and 2 to 5 parts of humic acid;
[0007] The B component comprises, by weight: 70-100 parts of polyetheramine and 30-40 parts of diethyltoluenediamine.
[0008] The mass ratio of component A to component B is 1:1~1:3.
[0009] Further, the polyetheramine is one or more of D2000, D400, D230, T403, and T5000. Further, the polyetheramine is T5000.
[0010] Furthermore, the mass ratio of component A to component B is 1:1.
[0011] Furthermore, the polymer coating of the composite rod surface protective coating that can be quickly hardened at room temperature is composed of component A and component B, wherein component A includes, by mass: 40 parts of polyether polyol, 30 parts of diphenylmethane-4,4'-diisocyanate, 30 parts of hexamethylene diisocyanate, 5 parts of dibutyl phthalate, 7 parts of hexadecylpyridinium bromide surface-modified chitosan-modified zeolite composite, and 2.5 parts of humic acid;
[0012] Component B includes, by mass: 70 parts of T5000 polyetheramine and 30 parts of diethyltoluenediamine.
[0013] The mass ratio of component A to component B is 1:1.
[0014] Furthermore, the preparation method of the hexadecylpyridinium bromide surface-modified chitosan-modified zeolite composite is:
[0015] Take 20g of chitosan modified zeolite complex and add it to 320mL of cetylpyridinium bromide aqueous solution, reflux reaction at 40°C for 48h, centrifuge to obtain precipitate after the reaction, wash the precipitate with deionized water 10 times, and then dry at 50°C to obtain cetylpyridinium bromide surface modified chitosan modified zeolite complex.
[0016] Furthermore, the preparation method of the chitosan modified zeolite composite is:
[0017] 6 g of zeolite was added to 50 mL of 95% ethanol, the pH was adjusted to 3-5 with glacial acetic acid, 0.2 g of γ-aminobutyric acid was added, and the mixture was refluxed at 60°C for 3 h. After natural cooling, the mixture was centrifuged, and the precipitate was washed 3 times with deionized water and dried at 60°C for 24 h to obtain a modified zeolite.
[0018] 8 g of chitosan was dissolved in 400 mL of 2 wt.% acetic acid aqueous solution and stirred for 30 min to obtain a chitosan solution; 40 g of modified zeolite was dispersed in 400 mL of deionized water and stirred for 30 min to obtain a modified zeolite solution; the chitosan solution and the modified zeolite solution were mixed together, stirred for 1 h, the pH was adjusted to 10 with 2 M NaOH, stirred for another 1 h, and then centrifuged to obtain a precipitate, the precipitate was washed 3 times with deionized water, and then dried at 105° C. to obtain a chitosan modified zeolite complex.
[0019] Furthermore, the preparation method of the A component is:
[0020] Each component in component A was vacuum dehydrated at 110°C and -0.1Mpa for 3h; then polyether polyol, diphenylmethane-4,4'-diisocyanate and hexamethylene diisocyanate were mixed under nitrogen atmosphere, and then heated to 90°C and stirred for reaction for 5h; then dibutyl phthalate, hexadecylpyridinium bromide surface-modified chitosan modified zeolite complex and humic acid were added, and stirred for reaction at 90°C for another 1h to obtain component A.
[0021] Furthermore, the preparation method of the B component is:
[0022] Each component in component B was first dehydrated in vacuum at 110°C and -0.1 MPa for 3 h; then stirred at 70°C for 1 h in a nitrogen atmosphere to obtain component B.
[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0024] The coating can harden quickly at room temperature, which greatly shortens the construction time and curing cycle and improves construction efficiency. Environmentally friendly raw materials such as polyether polyols and polyether amines are used in the coating formula to reduce pollution to the environment. The combined effect of the surface-modified chitosan-modified zeolite complex with hexadecylpyridinium bromide and humic acid promotes the salt spray resistance of the coating. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0026] The preparation method of the hexadecylpyridinium bromide surface-modified chitosan-modified zeolite composite of the present invention is as follows:
[0027] Take 20g of chitosan modified zeolite complex and add it to 320mL of cetylpyridinium bromide aqueous solution, reflux reaction at 40°C for 48h, centrifuge to obtain precipitate after the reaction, wash the precipitate with deionized water 10 times, and then dry at 50°C to obtain cetylpyridinium bromide surface modified chitosan modified zeolite complex.
[0028] The preparation method of the chitosan modified zeolite composite is as follows:
[0029] 6 g of zeolite was added to 50 mL of 95% ethanol, the pH was adjusted to 3-5 with glacial acetic acid, 0.2 g of γ-aminobutyric acid was added, and the mixture was refluxed at 60°C for 3 h. After natural cooling, the mixture was centrifuged, and the precipitate was washed 3 times with deionized water and dried at 60°C for 24 h to obtain a modified zeolite.
[0030] 8 g of chitosan was dissolved in 400 mL of 2 wt.% acetic acid aqueous solution and stirred for 30 min to obtain a chitosan solution; 40 g of modified zeolite was dispersed in 400 mL of deionized water and stirred for 30 min to obtain a modified zeolite solution; the chitosan solution and the modified zeolite solution were mixed together, stirred for 1 h, the pH was adjusted to 10 with 2 M NaOH, stirred for another 1 h, and then centrifuged to obtain a precipitate, the precipitate was washed 3 times with deionized water, and then dried at 105° C. to obtain a chitosan modified zeolite complex.
[0031] The preparation method of the chitosan modified zeolite composite of the present invention is as follows:
[0032] 6 g of zeolite was added to 50 mL of 95% ethanol, the pH was adjusted to 3-5 with glacial acetic acid, 0.2 g of γ-aminobutyric acid was added, and the mixture was refluxed at 60°C for 3 h. After natural cooling, the mixture was centrifuged, and the precipitate was washed 3 times with deionized water and dried at 60°C for 24 h to obtain a modified zeolite.
[0033] 8 g of chitosan was dissolved in 400 mL of 2 wt.% acetic acid aqueous solution and stirred for 30 min to obtain a chitosan solution; 40 g of modified zeolite was dispersed in 400 mL of deionized water and stirred for 30 min to obtain a modified zeolite solution; the chitosan solution and the modified zeolite solution were mixed together, stirred for 1 h, the pH was adjusted to 10 with 2 M NaOH, stirred for another 1 h, and then centrifuged to obtain a precipitate, the precipitate was washed 3 times with deionized water, and then dried at 105° C. to obtain a chitosan modified zeolite complex.
[0034] The preparation method of the hexadecylpyridinium bromide surface-modified chitosan zeolite composite in the present invention is as follows:
[0035] Take 20g of chitosan modified zeolite complex and add it to 320mL of cetylpyridinium bromide aqueous solution, reflux reaction at 40°C for 48h, centrifuge to obtain precipitate after the reaction, wash the precipitate with deionized water 10 times, and then dry at 50°C to obtain cetylpyridinium bromide surface modified chitosan modified zeolite complex.
[0036] The preparation method of the chitosan modified zeolite composite is as follows:
[0037] 8 g of chitosan was dissolved in 400 mL of 2 wt.% acetic acid aqueous solution and stirred for 30 min to obtain a chitosan solution; 40 g of zeolite was dispersed in 400 mL of deionized water and stirred for 30 min to obtain a zeolite solution; the chitosan solution and the zeolite solution were mixed together, stirred for 1 h, the pH was adjusted to 10 with 2 M NaOH, stirred for another 1 h, and then centrifuged to obtain a precipitate, the precipitate was washed 3 times with deionized water, and then dried at 105° C. to obtain a chitosan zeolite complex.
[0038] Example 1: Composite material rod surface protective coating A polymer coating that can be quickly hardened at room temperature, composed of component A and component B, wherein component A includes, by mass: 40 parts of polyether polyol, 30 parts of diphenylmethane-4,4'-diisocyanate, 30 parts of hexamethylene diisocyanate, 5 parts of dibutyl phthalate, 1 part of hexadecylpyridinium bromide surface-modified chitosan-modified zeolite composite, and 2.5 parts of humic acid;
[0039] Component B includes, by mass: 70 parts of T5000 polyetheramine and 30 parts of diethyltoluenediamine.
[0040] The mass ratio of component A to component B is 1:1.
[0041] The preparation method comprises the following steps: vacuum dehydrating each component in component A at 110°C and -0.1Mpa for 3 hours; then mixing polyether polyol, diphenylmethane-4,4'-diisocyanate and hexamethylene diisocyanate under a nitrogen atmosphere, heating to 90°C, and stirring for reaction for 5 hours; then adding dibutyl phthalate, hexadecylpyridinium bromide surface-modified chitosan-modified zeolite complex and humic acid, stirring for reaction at 90°C for another hour, and obtaining component A;
[0042] Each component in component B was first dehydrated in vacuum at 110°C and -0.1 MPa for 3 h; then stirred at 70°C for 1 h in a nitrogen atmosphere to obtain component B.
[0043] Example 2: Composite material rod surface protective coating A polymer coating that can be quickly hardened at room temperature, composed of component A and component B, wherein component A includes, by mass: 40 parts of polyether polyol, 30 parts of diphenylmethane-4,4'-diisocyanate, 30 parts of hexamethylene diisocyanate, 5 parts of dibutyl phthalate, 3 parts of hexadecylpyridinium bromide surface-modified chitosan-modified zeolite composite, and 2.5 parts of humic acid;
[0044] Component B includes, by mass: 70 parts of T5000 polyetheramine and 30 parts of diethyltoluenediamine.
[0045] The mass ratio of component A to component B is 1:1.
[0046] The preparation method comprises the following steps: vacuum dehydrating each component in component A at 110°C and -0.1Mpa for 3 hours; then mixing polyether polyol, diphenylmethane-4,4'-diisocyanate and hexamethylene diisocyanate under a nitrogen atmosphere, heating to 90°C, and stirring for reaction for 5 hours; then adding dibutyl phthalate, hexadecylpyridinium bromide surface-modified chitosan-modified zeolite complex and humic acid, stirring for reaction at 90°C for another hour, and obtaining component A;
[0047] Each component in component B was first dehydrated in vacuum at 110°C and -0.1 MPa for 3 h; then stirred at 70°C for 1 h in a nitrogen atmosphere to obtain component B.
[0048] Example 3: Composite material rod surface protective coating A polymer coating that can be quickly hardened at room temperature, composed of component A and component B, wherein component A includes, by mass: 40 parts of polyether polyol, 30 parts of diphenylmethane-4,4'-diisocyanate, 30 parts of hexamethylene diisocyanate, 5 parts of dibutyl phthalate, 5 parts of hexadecylpyridinium bromide surface-modified chitosan-modified zeolite composite, and 2.5 parts of humic acid;
[0049] Component B includes, by mass: 70 parts of T5000 polyetheramine and 30 parts of diethyltoluenediamine.
[0050] The mass ratio of component A to component B is 1:1.
[0051] The preparation method comprises the following steps: vacuum dehydrating each component in component A at 110°C and -0.1Mpa for 3 hours; then mixing polyether polyol, diphenylmethane-4,4'-diisocyanate and hexamethylene diisocyanate under a nitrogen atmosphere, heating to 90°C, and stirring for reaction for 5 hours; then adding dibutyl phthalate, hexadecylpyridinium bromide surface-modified chitosan-modified zeolite complex and humic acid, stirring for reaction at 90°C for another hour, and obtaining component A;
[0052] Each component in component B was first dehydrated in vacuum at 110°C and -0.1 MPa for 3 h; then stirred at 70°C for 1 h in a nitrogen atmosphere to obtain component B.
[0053] Example 4: Composite material rod surface protective coating A polymer coating that can be quickly hardened at room temperature, composed of component A and component B, wherein component A includes, by mass: 40 parts of polyether polyol, 30 parts of diphenylmethane-4,4'-diisocyanate, 30 parts of hexamethylene diisocyanate, 5 parts of dibutyl phthalate, 7 parts of hexadecylpyridinium bromide surface-modified chitosan-modified zeolite composite, and 2.5 parts of humic acid;
[0054] Component B includes, by mass: 70 parts of T5000 polyetheramine and 30 parts of diethyltoluenediamine.
[0055] The mass ratio of component A to component B is 1:1.
[0056] The preparation method comprises the following steps: vacuum dehydrating each component in component A at 110°C and -0.1Mpa for 3 hours; then mixing polyether polyol, diphenylmethane-4,4'-diisocyanate and hexamethylene diisocyanate under a nitrogen atmosphere, heating to 90°C, and stirring for reaction for 5 hours; then adding dibutyl phthalate, hexadecylpyridinium bromide surface-modified chitosan-modified zeolite complex and humic acid, stirring for reaction at 90°C for another hour, and obtaining component A;
[0057] Each component in component B was first dehydrated in vacuum at 110°C and -0.1 MPa for 3 h; then stirred at 70°C for 1 h in a nitrogen atmosphere to obtain component B.
[0058] Example 5: Composite material rod surface protective coating A polymer coating that can be quickly hardened at room temperature, composed of component A and component B, wherein component A includes, by mass: 40 parts of polyether polyol, 30 parts of diphenylmethane-4,4'-diisocyanate, 30 parts of hexamethylene diisocyanate, 5 parts of dibutyl phthalate, 10 parts of hexadecylpyridinium bromide surface-modified chitosan-modified zeolite composite, and 2.5 parts of humic acid;
[0059] Component B includes, by mass: 70 parts of T5000 polyetheramine and 30 parts of diethyltoluenediamine.
[0060] The mass ratio of component A to component B is 1:1.
[0061] The preparation method comprises the following steps: vacuum dehydrating each component in component A at 110°C and -0.1Mpa for 3 hours; then mixing polyether polyol, diphenylmethane-4,4'-diisocyanate and hexamethylene diisocyanate under a nitrogen atmosphere, heating to 90°C, and stirring for reaction for 5 hours; then adding dibutyl phthalate, hexadecylpyridinium bromide surface-modified chitosan-modified zeolite complex and humic acid, stirring for reaction at 90°C for another hour, and obtaining component A;
[0062] Each component in component B was first dehydrated in vacuum at 110°C and -0.1 MPa for 3 h; then stirred at 70°C for 1 h in a nitrogen atmosphere to obtain component B.
[0063] Comparative Example 1: A composite material rod surface protective coating, a polymer coating that can be quickly hardened at room temperature, is composed of component A and component B, wherein component A includes, by mass: 40 parts of polyether polyol, 30 parts of diphenylmethane-4,4'-diisocyanate, 30 parts of hexamethylene diisocyanate, 5 parts of dibutyl phthalate, 7 parts of chitosan-modified zeolite composite, and 2.5 parts of humic acid;
[0064] Component B includes, by mass: 70 parts of T5000 polyetheramine and 30 parts of diethyltoluenediamine.
[0065] The mass ratio of component A to component B is 1:1.
[0066] The preparation method is as follows: vacuum dehydrating each component in component A at 110°C and -0.1Mpa for 3 hours; then mixing polyether polyol, diphenylmethane-4,4'-diisocyanate and hexamethylene diisocyanate under a nitrogen atmosphere, heating to 90°C, stirring and reacting for 5 hours; then adding dibutyl phthalate, chitosan-modified zeolite composite and humic acid, stirring and reacting at 90°C for another hour to obtain component A;
[0067] Each component in component B was first dehydrated in vacuum at 110°C and -0.1 MPa for 3 h; then stirred at 70°C for 1 h in a nitrogen atmosphere to obtain component B.
[0068] Comparative Example 2: A composite material rod surface protective coating, a polymer coating that can be quickly hardened at room temperature, is composed of component A and component B, wherein component A includes, by mass: 40 parts of polyether polyol, 30 parts of diphenylmethane-4,4'-diisocyanate, 30 parts of hexamethylene diisocyanate, 5 parts of dibutyl phthalate, 7 parts of hexadecylpyridinium bromide surface-modified chitosan zeolite composite, and 2.5 parts of humic acid;
[0069] Component B includes, by mass: 70 parts of T5000 polyetheramine and 30 parts of diethyltoluenediamine.
[0070] The mass ratio of component A to component B is 1:1.
[0071] The preparation method is as follows: vacuum dehydrating each component in component A at 110°C and -0.1Mpa for 3 hours; then mixing polyether polyol, diphenylmethane-4,4'-diisocyanate and hexamethylene diisocyanate under a nitrogen atmosphere, heating to 90°C, and stirring for reaction for 5 hours; then adding dibutyl phthalate, hexadecylpyridinium bromide surface-modified chitosan zeolite complex and humic acid, stirring for reaction at 90°C for another hour, and obtaining component A;
[0072] Each component in component B was first dehydrated in vacuum at 110°C and -0.1 MPa for 3 h; then stirred at 70°C for 1 h in a nitrogen atmosphere to obtain component B.
[0073] Comparative Example 3: A composite material rod surface protective coating, a polymer coating that can be quickly hardened at room temperature, is composed of component A and component B, wherein component A includes, by mass: 40 parts of polyether polyol, 30 parts of diphenylmethane-4,4'-diisocyanate, 30 parts of hexamethylene diisocyanate, 5 parts of dibutyl phthalate, and 7 parts of hexadecylpyridinium bromide surface-modified chitosan-modified zeolite composite;
[0074] Component B includes, by mass: 70 parts of T5000 polyetheramine and 30 parts of diethyltoluenediamine.
[0075] The mass ratio of component A to component B is 1:1.
[0076] The preparation method is as follows: vacuum dehydrating each component in component A at 110°C and -0.1Mpa for 3 hours; then mixing polyether polyol, diphenylmethane-4,4'-diisocyanate and hexamethylene diisocyanate under a nitrogen atmosphere, heating to 90°C, and stirring for reaction for 5 hours; then adding dibutyl phthalate and hexadecylpyridinium bromide to modify the surface of the chitosan-modified zeolite composite, stirring for reaction at 90°C for another hour, and obtaining component A;
[0077] Each component in component B was first dehydrated in vacuum at 110°C and -0.1 MPa for 3 h; then stirred at 70°C for 1 h in a nitrogen atmosphere to obtain component B.
[0078] Comparative Example 4: A composite material rod surface protective coating, a polymer coating that can be quickly hardened at room temperature, is composed of component A and component B, wherein component A includes, by mass: 40 parts of polyether polyol, 30 parts of diphenylmethane-4,4'-diisocyanate, 30 parts of hexamethylene diisocyanate, 5 parts of dibutyl phthalate, and 2.5 parts of humic acid;
[0079] Component B includes, by mass: 70 parts of T5000 polyetheramine and 30 parts of diethyltoluenediamine.
[0080] The mass ratio of component A to component B is 1:1.
[0081] The preparation method is as follows: vacuum dehydrating each component in component A at 110°C and -0.1Mpa for 3 hours; then mixing polyether polyol, diphenylmethane-4,4'-diisocyanate and hexamethylene diisocyanate under a nitrogen atmosphere, heating to 90°C, and stirring for reaction for 5 hours; then adding dibutyl phthalate and humic acid, stirring for reaction at 90°C for another hour, and obtaining component A;
[0082] Each component in component B was first dehydrated in vacuum at 110°C and -0.1 MPa for 3 h; then stirred at 70°C for 1 h in a nitrogen atmosphere to obtain component B.
[0083] Test Example 1
[0084] The polymer coating A and B components of the composite pole surface protective coating prepared in each embodiment and comparative example, which can be quickly hardened at room temperature, are mixed evenly and then sprayed on the surface of the composite pole by a spray gun, so that the overall thickness of the coating is not less than 0.5 mm, and naturally cured for 3 days. The artificial accelerated aging performance refers to GB / T1865-2009, and the salt spray resistance refers to GB / T1771-2007. The composite pole is a composite pole with polyurethane or epoxy as the matrix and glass fiber as the reinforcement, and the raw material ratio is accurately controlled by a four-dimensional winding machine and wet winding is formed.
[0085] Table 1 Performance test
[0086] Salt spray resistance Artificial accelerated aging performance Example 1 1100h pass Example 2 1100h pass Example 3 1300h pass Example 4 1350h pass Example 5 1200h pass Comparative Example 1 900h pass Comparative Example 2 800h pass Comparative Example 3 950h pass Comparative Example 4 600h Not passed
[0087] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. Composite material rod surface protective coating is a polymer coating that hardens quickly at room temperature, characterized in that: The invention is composed of component A and component B, wherein component A comprises, by mass, 40 to 60 parts of polyether polyol, 25 to 40 parts of diphenylmethane-4,4'-diisocyanate, 25 to 40 parts of hexamethylene diisocyanate, 3 to 10 parts of dibutyl phthalate, 1 to 10 parts of chitosan modified zeolite composite surface modified with hexadecylpyridinium bromide, and 2 to 5 parts of humic acid; Component B includes, by mass: 70-100 parts of polyetheramine and 30-40 parts of diethyltoluenediamine; The mass ratio of component A to component B is 1:1~1:3; The preparation method of the hexadecylpyridinium bromide surface-modified chitosan-modified zeolite composite is as follows: 20 g of chitosan-modified zeolite complex was added to 320 mL of cetylpyridinium bromide aqueous solution, and refluxed at 40° C. for 48 h. After the reaction, the precipitate was obtained by centrifugation. The precipitate was washed 10 times with deionized water, and then dried at 50° C. to obtain a cetylpyridinium bromide surface-modified chitosan-modified zeolite complex; The preparation method of the chitosan modified zeolite composite is: 6 g of zeolite was added to 50 mL of 95% ethanol, the pH was adjusted to 3-5 with glacial acetic acid, 0.2 g of γ-aminobutyric acid was added, and the mixture was refluxed at 60°C for 3 h. After natural cooling, the mixture was centrifuged, and the precipitate was washed 3 times with deionized water and dried at 60°C for 24 h to obtain a modified zeolite. 8 g of chitosan was dissolved in 400 mL of 2 wt.% acetic acid aqueous solution and stirred for 30 min to obtain a chitosan solution; 40 g of modified zeolite was dispersed in 400 mL of deionized water and stirred for 30 min to obtain a modified zeolite solution; the chitosan solution and the modified zeolite solution were mixed together, stirred for 1 h, the pH was adjusted to 10 with 2 M NaOH, stirred for another 1 h, and then centrifuged to obtain a precipitate, the precipitate was washed 3 times with deionized water, and then dried at 105° C. to obtain a chitosan modified zeolite complex.
2. The polymer coating for composite rod surface protection coating that hardens rapidly at room temperature according to claim 1, characterized in that: The polyetheramine is one or more of D2000, D400, D230, T403 and T5000.
3. The polymer coating for composite rod surface protection coating that hardens rapidly at room temperature according to claim 2, characterized in that: The polyetheramine is T5000.
4. The polymer coating for composite rod surface protection coating that hardens rapidly at room temperature according to claim 1, characterized in that: The mass ratio of the A component to the B component is 1:
1.
5. The polymer coating for composite rod surface protection coating that hardens rapidly at room temperature according to claim 1, characterized in that: The invention is composed of component A and component B, wherein component A comprises, by mass, 40 parts of polyether polyol, 30 parts of diphenylmethane-4,4'-diisocyanate, 30 parts of hexamethylene diisocyanate, 5 parts of dibutyl phthalate, 7 parts of hexadecylpyridinium bromide surface-modified chitosan-modified zeolite composite, and 2.5 parts of humic acid; Component B includes, by mass: 70 parts of T5000 polyetheramine and 30 parts of diethyltoluenediamine; The mass ratio of component A to component B is 1:
1.
6. The polymer coating for the composite rod surface protective coating that hardens rapidly at room temperature according to claim 1, characterized in that: The preparation method of the A component is: Each component in component A was vacuum dehydrated at 110°C and -0.1MPa for 3h; then, polyether polyol, diphenylmethane-4,4'-diisocyanate and hexamethylene diisocyanate were mixed under a nitrogen atmosphere, and then heated to 90°C and stirred for reaction for 5h; then, dibutyl phthalate, hexadecylpyridinium bromide surface-modified chitosan-modified zeolite complex and humic acid were added, and the mixture was stirred for reaction at 90°C for another 1h to obtain component A.
7. The polymer coating for the composite rod surface protective coating that hardens rapidly at room temperature according to claim 1, characterized in that: The preparation method of the B component is: Each component in component B was first dehydrated in vacuum at 110°C and -0.1MPa for 3 h; then stirred at 70°C for 1 h in a nitrogen atmosphere to obtain component B.
Citation Information
Patent Citations
Inorganic / organic nano composite antibacterial agent and its fabric product application
CN101189971A
Composition for ordinary temperature curing polyurethane coating film material and construction method of ordinary temperature curing polyurethane coating film material
JP2016098309A